Asexuality and epistemic injustice: a gendered perspective - Cuthbert, Karen (Journal of Gender Studies, 2022)
Drawing on original qualitative research, I argue that the concept of ‘epistemic injustice’ proposed by the feminist philosopher Miranda Fricker, and located within a long genealogy of Black feminist scholarship, can be used sociologically to help understand the lived experiences of asexual people. I show how participants’ accounts of their asexual subjectivities were frequently denied, dismissed and over-written. However, I argue that these experiences were heavily gendered, in that asexual women were subject to epistemic injustices to a degree and in ways that their male counterparts were not, and that this must be understood within the power relations of hetero-patriarchy. These epistemic injustices revolved around old yet prevailing constructions of femininity and womanhood as ‘naturally’ asexual, passive, and lacking agency. When asexual men experienced epistemic injustice, this was rooted in familiar understandings of masculinity as necessitating an active and desiring sexuality. Using Fricker’s elucidation of hermeneutical and testimonial forms of epistemic injustice, I show how asexuality remains a culturally unfamiliar hermeneutical frame in a context of ‘compulsory sexuality’ but also how stories of asexuality are ‘heard’ based on the gendered (and unequal) distribution of testimonial credibility.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asexualité; cours; cycles supérieurs; discipline; europe; fem9000; injustices épistémiques; patriarcat; périodes historiques; royaume-uni; régions géographiques; sciences humaines; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; violences; études de genres

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Gouverner la vie privée: l'encadrement inégalitaire des séparations conjugales en France et au Québec - Biland, Émilie (Gouvernement en question(s), 2019)
"L'implication de l'État dans la vie privée pose problème : les individus ont davantage de droits que par le passé, mais certains de leurs comportements, jugés problématiques pour la collectivité, justifient un interventionnisme renouvelé, dans lequel acteurs privés et mécanismes de marché occupent une place croissante. En tension entre libéralisme et normalisation, cette action publique participe aux recompositions des rapports sociaux, entre les classes sociales, entre les genres, ainsi qu'entre la population majoritaire et les personnes racisées. Objet de vifs débats et de réformes récurrentes, la régulation par le droit des séparations conjugales est un observatoire précieux de ces recompositions, ici analysées à partir de trois enquêtes collectives, qualitatives et quantitatives, menées des deux côtés de l'Atlantique. En France comme au Québec, l'accès aux procédures, les interactions avec les professionnel.les et l'encadrement des modes de vie sont les trois dimensions constitutives du gouvernement de la vie privée. Cependant, chacun des contextes n'articule pas de la même manière inégalités de classe et inégalités de genre. En scrutant la production institutionnelle des inégalités privées, cet ouvrage invite à imaginer des voies alternatives, dans la sphère privée comme dans la sphère publique, pour que la politique des droits tienne ses promesses émancipatrices."
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; droit des femmes*; droits des femmes*; europe; famille; france; hétérosexualité; inégalités; mariage; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; soc2262; soc2264; sociologie; systèmes d'oppressions; séparation; thématiques

The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

The Black girlhood studies collection - Halliday, Aria S. (Women's Press, an imprint of CSP Books Inc., 2019)
Ce texte révolutionnaire est l'une des premières collections à explorer, développer et évaluer exclusivement les théories des filles noires et des jeunes filles noires. Ce volume rassemble des universitaires émergent.e.s et établi.e.s d'Amérique du Nord pour discuter de ce que la jeune fille noire signifie historiquement au 21e siècle, et comment les concepts de race, d'ethnicité, de sexe, de sexualité, de classe, de religion et de nationalité informent ou affectent l'identité des filles noires. au-delà de l'école ou du milieu urbain. Divisé en deux sections, les sujets couverts incluent le féminisme noir, l'intersectionnalité, le plaisir et l'agentivité érotique, l'activisme des médias et des fans, la construction de soi, le leadership, le changement social, la masculinité toxique et les soins personnels. La collection d'études sur les filles noires est une ressource vitale qui évoquera des discussions et des changements significatifs pour les étudiant.e.s en études africaines, études sur les Noir.e.s, études sur les enfants et les jeunes, études sur le genre et les femmes, études sur les médias et cours de sociologie dans le monde. CARACTÉRISTIQUES: - s'engage dans les contributions d'universitaires émergents et établis provenant d'un large éventail de disciplines et d'horizons divers - comprend des fonctionnalités pédagogiques telles que des introductions et des conclusions de chapitre, des mots-clés, des questions de discussion et des glossaires
Keywords: 2000 à aujourd'hui; 2010-2019; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; fem3300; filles noires; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; racisme; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences

Theorizing black girlhood - Smith, Ashley L. (The black girlhood studies collection, 2019)
Keywords: 2000 à aujourd'hui; 2010-2019; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; fem3300; filles noires; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; racisme; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences

Des sexes innombrables: le genre à l'épreuve de la biologie - Hoquet, Thierry (Science ouverte, 2016)
Combient y-at-il de sexes? "Deux!", répond l'opinion. "Deux" répond la science. Heureuse concordance : c'est donc que l'opinion a raison, conclura-t-on. Mais est-on si certain que l'opinion et la science disent, sur la question du sexe, la même chose? Quand l'opinion affirme qu'il y a deux sexes, elle soutient qu'il existe, dans chaque espèce, deux types d'individus et seulement deux. Il y aurait alors le masculin et le féminin. Mais quand la science avance qu'il y a deux sexes, que vise-t-elle ? Quelle est, pour un biologiste, la signification des termes "mâle" et "femelle" ? En tentant de compter les sexes, on doit bientôt se risquer à distinguer le normal du pathologique.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; discipline; europe; france; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe biologique; sexisme; sexualité; systèmes d'oppressions; thématiques

Luttes féministes autour du consentement: Héritages et impensés des mobilisations contemporaines sur la gynécologie - Quéré, Lucile (Nouvelles Questions Féministes, 2016)
L'étude des mobilisations françaises de l'année 2014-2015 autour de la gynécologie permet d'interroger les différentes manières dont les mouvements féministes se sont saisis de la notion de consentement. Théorisé par les féministes à propos de la sexualité, le consentement est apparu comme un des principes fondateurs d'une morale sexuelle féministe. Les mouvements de 2014, portés par des militantes de la cause des femmes, (ré)introduisent cette notion dans le cabinet médical, et l'appliquent notamment à l'interaction gynécologique. Cela leur permet d'utiliser la loi française de 2002 sur les droits des patient·e·s comme un outil de politisation du cabinet gynécologique et de remise en cause des pratiques et des discours des soignant·e·s à l'égard des femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; care; cours; discipline; discours dominant; europe; france; inégalités; justice sociale; militance; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; santé; santé des femmes*; sciences humaines; sexisme; sexualité; systèmes d'oppressions; thématiques